مواقف السياسة الخارجية للدولة الخوارزمية وأثرها في توجيه الأحداث السياسية قبيل الغزو المغولي (490 ه- 615 ه/1096م- 1218م) - قادري حمزة (University of Eloued جامعة الوادي, 2024)
تهدف هذه الدراسة إلى البحث في مواقف السياسة الخارجية للدولة الخوارزمية مع القوى السياسية الحاكمة في شرق العالم الإسلامي (السلاجقة والعباسيين والغوريين ودولة الخطا) منذ تولي قطب الدين محمد بن أنوشتكين سنة 490ه/ 1096م حكم ولاية خوارزم عن السلاجقة أصحاب السلطة على تلك الأقاليم وقتذاك؛ وإلى استقلالهم بحكمها على عهد أتسز بن قطب الدين ودخولهم في خط سياسي مستقل يهدف إلى بناء إمبراطورية ممتدة الأرجاء على حساب محيطهم؛ فكان عليهم بغية تحقيق أهدافهم السياسية اتخاذ جملة من المواقف على مستوى السياسة الخارجية تراوحت بين السلمية والصداقة أحيانًا وبين العنف والدخول في حروب عسكرية أحيانًا أخرى، وهذا طيلة سنوات القرن السادس الهجري/ الثاني عشر الميلادي، لترتسم انطلاقا من تلك المواقف – بحكم حجم نفوذ دولة الخوارزميين- صورة الواقع السياسي للعالم الإسلامي بأحداثه الأليمة خلال النصف الأول من القرن السابع الهجري/ الثالث عشر الميلادي بغزو المغول لديار الإسلام. This study aims to investigate the foreign policy positions of the Khwarezm state with the ruling political forces in the eastern Islamic world (the Seljuks, the Abbasids, the Ghurids, and the Khitta state) since Qutb al-Din Muhammad ibn Anushtakin assumed the rule of the Khwarezm state in the year 490 AH/1096 AD from the Seljuks who had authority over those regions at that time. And to their independence under its rule during the reign of Atsiz bin Qutb al-Din and their entry into an independent political line aimed at building a far-reaching empire at the expense of their surroundings; In order to achieve their political goals, they had to take a number of positions at the level of foreign policy, ranging from peace and friendship at times to violence and entering into military wars at other times. This occurred throughout the years of the sixth century AH/twelfth century AD. Based on these positions - due to the extent of the influence of the Khwarezmian state - a picture of the political reality of the Islamic world with its painful events during the first half of the seventh century AH / thirteenth century AD with the Mongols’ invasion of the lands of Islam emerges.
Keywords: الخوارزميون; السلاجقة; السياسة الخارجية; المغول; علاء الدين خوارزمشاه; Al-Khwarizmians; Seljuks; Foreign Policy; Mongols; Aladdin Khwarezmshah